Identifying the Pockets Most Affected by Temperature Rise and Evaluating the Repercussions on Urban Communities and Their Agricultural Lands - Giath Doun; Osama Darwish; Nilanchal Patel; Alaa Mhawish; Hashem Sharba (Remote Sensing)
Climate data consistently indicate a rising temperature trend and a simultaneous decline in precipitation across Syria. Empirical records confirm projections of intensifying drought conditions throughout the Middle East, including Syria, with an increasing frequency, severity, and duration of drought events. However, a major challenge in assessing climate trends is the significant spatial and temporal gaps in Syria’s meteorological records. These gaps stem from the uneven distribution of weather stations—primarily located in populated areas, often lacking automation—and the widespread destruction of stations due to the ongoing civil war, which has coincided with worsening climate impacts. To address these challenges, in this study, an integrated methodology was developed leveraging remote sensing (RS) and geographic information system (GIS) techniques to identify the regions most affected by rising temperatures. While previous research has primarily analyzed the overall trend of meteorological drought in Syria, this study uniquely focuses on temperature rise at a national scale, systematically identifying the most severely impacted areas. Our analysis reveals 23 highly affected regions covering over 31,000 square kilometers, with significant current and projected consequences. These hotspots currently expose over 2.5 million people to thermal drought and encompass approximately 25% of Syria’s agricultural land, intensifying food security vulnerabilities. Notably, some of these affected pockets are in historically settled areas—previously considered resilient to direct climate change impacts—such as the coastal region. Given that Syria has endured a protracted crisis for thirteen years, the compounded effects of climate change further exacerbate daily hardships for millions, driving both internal displacement and migration, particularly toward Europe. This study underscores the urgent need for climate-responsive policies to mitigate the socio-economic and environmental repercussions of rising temperatures in Syria.